2011
DOI: 10.1037/a0022758
|View full text |Cite
|
Sign up to set email alerts
|

Happy mouth and sad eyes: Scanning emotional facial expressions.

Abstract: There is evidence that specific regions of the face such as the eyes are particularly relevant for the decoding of emotional expressions, but it has not been examined whether scan paths of observers vary for facial expressions with different emotional content. In this study, eye-tracking was used to monitor scanning behavior of healthy participants while looking at different facial expressions. Locations of fixations and their durations were recorded, and a dominance ratio (i.e., eyes and mouth relative to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

45
357
12
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 363 publications
(422 citation statements)
references
References 50 publications
45
357
12
8
Order By: Relevance
“…In line with eye movement monitoring studies (Bombardi et al, 2013;Eisenbarth & Alpers, 2011) the current study suggests that both the mouth and eyes are important for the processing of fearful faces, not just the eyes as suggested by others (e.g., Schyns et al, 2007Schyns et al, , 2009Smith et al, 2005). It is important to note, however, that these results might be specific to the current emotion discrimination task.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In line with eye movement monitoring studies (Bombardi et al, 2013;Eisenbarth & Alpers, 2011) the current study suggests that both the mouth and eyes are important for the processing of fearful faces, not just the eyes as suggested by others (e.g., Schyns et al, 2007Schyns et al, , 2009Smith et al, 2005). It is important to note, however, that these results might be specific to the current emotion discrimination task.…”
Section: Discussionsupporting
confidence: 88%
“…This result supports recent behavioural studies that have demonstrated the importance of the mouth region in the discrimination of fearful expressions (Blais et al, 2012) and visual scanning studies where participants made saccades equally towards the eyes and mouth of fearful faces (e.g. Eisenbarth & Alpers, 2011; see also Bombardi et al, 2013). These modulations of the neural activity with fixation to eyes and mouth seen in the present studies for fearful and happy expressions contrast with a lack of such effects in our previous gender discrimination task (Neath & Itier, 2015), pointing at possible effects of task demands on the use of featural information that future studies will have to elucidate further using task as a within-subject factor.…”
Section: Fearful Expression Processing: It's Not That Early and It's supporting
confidence: 90%
“…Importantly, this feature integration (holistic processing) is dependent on presentation time as we showed an increase in performance with increasing presentation time. In contrast, eye-tracking studies have shown that when the entire face is presented for 150 ms and above, participants look longer and/or make more fixations to the diagnostic features (e.g., Eisenbarth & Alpers, 2011;Gamer & Büchel, 2009;Scheller et al, 2012). However, while these studies support the idea that diagnostic features play a role in the gaze exploration of facial expressions, they do not demonstrate that this gaze pattern difference explains emotion discrimination performances.…”
Section: Discussionmentioning
confidence: 73%
“…Similarly, Gamer and Büchel (2009) showed that although participants usually moved their eyes more toward than away from the eyes, they did so more for fearful and neutral faces than for happy or angry faces. In contrast, Eisenbarth and Alpers (2011) showed that the eyes received more attention for sad and angry faces, the mouth for happy faces, but that both features were equally important for fearful and neutral faces. In a famous neuropsychological study, Adolphs et al (2005) reported that instructing a patient with amygdala damage to focus on the eye region of a fearful expression improved her ability to recognise fear to the same level as control patients.…”
mentioning
confidence: 65%
“…In typical perceivers, the proportion of dwell time spent on the eye and mouth regions has also been found to vary according to emotional expression, such that participants are drawn to the eye region for sad faces and the mouth region for happy faces (Eisenbarth & Alpers, 2011). A novel application of this finding is to examine whether the same biases can be observed in EM, in order to investigate whether any abnormalities in regional scanning are absolute or still follow typical trends, albeit at a reduced level.…”
Section: Rehabilitation Of Prosopagnosia 16mentioning
confidence: 99%